HUBUNGAN MAHASISWA BERWIRAUSAHA TERHADAP PRESTASINYA DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Tri Hesniati; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted on the campus of the Faculty of Social and Political Sciences, Riau University, which is located on Jalan HR Soebrantas, Tampan district, Riau. The purpose of this research is to find out: 1) To find out  the level of student activity description is entrepreneurship. 2) To find out  the level of achievement picture (academic, non-academic and study mass) of students who carry out entrepreneurial activities. 3) To find out the relationship between entrepreneurial student activities and student achievement. This study uses a quantitative analysis approach. The population in this study are active students of FISIP UNRI who have a business or business either individually or in groups and online or offline totaling 33 people from 3 different majors where data can be obtained from the Dean of FISIP UNRI for Student Affairs. The sampling technique used the census method. The data instrument is a questionnaire. Based on the results of the study, it can be concluded that the entrepreneurial activity of students at the Faculty of Social and Political Sciences, Riau University, 12 people (36.4%) are in the sufficient category, 2 people (6.1%) are in the low category and 19 people (57, 6%) are in the high category. Achievement of entrepreneurship students at the Faculty of Social and Political Sciences, Riau University, as many as 21 people (63.6%) were in the moderate category, 10 people (30.3%) were in the high category and 2 people (6.1%) were in the low category. low category. The results of the person product moment co-operation test can be found that the significant value between the entrepreneurial activity variable and student achievement is 0.145, because the value of sig. 0.145 > 0.05. The value of the correlation coefficient between the entrepreneurial activity variable and student achievement is 0.259, which means it is positive. Furthermore, because the coefficient value of 0.259 is in the second interval, which is between 0.20-0.399, so it can be said that the level of relationship between entrepreneurship activities and student achievement is low. Keywords : Student, Achievement, Entrepreneurship